AKIBAT HUKUM ATAS MUSNAHNYA JAMINAN FIDUSIA DALAM PERJANJIAN KREDIT STUDI KASUS PT. BPR HARAU - Rizky, Lailatul; Suryamizon, Anggun Lestari; Adriaman, Mahlil (Ensiklopedia of Journal, 2023)
One of the objectives of the Republic of Indonesia based on the 1945 Constitution of the Republic of Indonesia is to create a prosperous, just, and prosperous society. In realizing these goals, national development activities are needed, especially development in the economic sector. In Indonesia there are several financial institutions that provide credit loans, such as pawnshops, non-bank financial institutions, and bank financial institutions both government and private. This research method used in this study is descriptive, namely legal research on the enactment or implementation of normative legal provisions in action on every particular legal event that occurs in society. Article 1444 of the Civil Code which states If a particular item which is the subject of the agreement is destroyed, can no longer be traded in such a way that it is not at all known whether it still exists, then abolish the bond, provided that the goods are destroyed beyond the fault of the debtor, and before he neglects to deliver them. Destruction referred to in the Fiduciary Guarantee Act is total destruction, where the object that is the fiduciary guarantee can no longer be used properly, even though a small part or the rest of the object still exists due to events beyond the fault of the parties. And the creditor has the right to an insurance claim from the destroyed object, the insurance claim is used as a substitute for the destroyed collateral object.